Estudo da incorporação de lantânio na zeólita beta na reação de tiofeno em uma corrente de cicloexano em condições de FCC - Nascimento Monteiro, Vanessa; Freire Almeida, Daniel; Cerqueira dos Santos Silva, Anderson; Lienthier da Silva, Amanda; Baldoino Silva, Zaíne; Costa Santos, Ronaldo; Magalhães Pontes, Luiz Antônio (XIV Encontro de Catálise do Norte, Nordeste e Centro-Oeste, 2024)
Strategies for desulfurization in refineries have become essential in response to increasingly stringent environmental regulations that reduce the sulfur limits in gasoline due to concerns over pollutant emissions. The Fluid Catalytic Cracking (FCC) unit plays a key role in gasoline production, making it crucial to develop technologies that maximize sulfur compound removal without compromising economic profitability. A promising approach involves the use of sulfur-reducing additives mixed with the FCC catalyst to achieve in situ reduction of these contaminants during the cracking reaction process. This study focuses on the catalytic cracking of thiophene in a cyclohexane stream using Beta zeolite (SAR 18) modified with lanthanum. The catalyst was prepared by diffusional wet impregnation, with a lanthanum content of approximately 6 wt%. Physicochemical characterizations, including XRF, XRD, structural FTIR, and N2 physisorption isotherms, were performed to compare the lanthanum catalyst (La-B) with the pure zeolite (H-B). The reaction was carried out at 500 °C using 250 mg of catalyst, with a WHSV of 3,7 h⁻¹, in a bench-scale testing unit designed for sulfur-containing molecule transformations, containing a coupled GC-FID/SCD. The sulfur content of 2 wt% (20000 ppm wt/wt) in cyclohexane was chosen to represent FCC feed conditions. Cyclohexane conversion ranged from 80-84 %mol, and thiophene conversion was 78-85 %mol. Both catalysts were selective towards cracking reactions of cyclohexane and thiophene, with a selectivity to H₂S range of 83-85 %mol. However, the lanthanum-incorporated catalyst proved more effective as a sulfur-reducing additive in gasoline, as it generated fewer condensed products and exhibited greater resistance to deactivation during both hydrocarbon and sulfur compound reactions.